A functionalized fluorescent dendrimer as a pesticide nanocarrier: application in pest control. Issue 2 (27th November 2014) - Liu, Xiaoxia; He, Bicheng; Xu, Zejun; Yin, Meizhen; Yang, Wantai; Zhang, Huaijiang; Cao, Jingjun; Shen, Jie
Abstract : A water-soluble fluorescent cationic dendrimer can efficiently deliver a pesticide into the insect cells and largely increase the cytotoxicity of the drug. Abstract : We report the delivery of a hydrophobic pesticide, thiamethoxam, by water-soluble nanosized cationic dendrimers that contain hydrophobic dendritic polyesters and peripheral amines, demonstrated by DLS, spectral analysis and ITC. The dendrimer-based nanocarrier can efficiently deliver the pesticide into the live cells and largely increase the cytotoxicity of the drug.